ANALYSIS OF PARENTING PATTERNS IN GUIDING BEGINNING READING IN DYSLEXIC CHILDREN IN ELEMENTARY SCHOOL - Fadhilah Ayu Puspitasari, Nur; Rezania, Vanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is aimed at finding out the type of parenting style applied by parents in guiding beginning reading in dyslexic children. This research uses qualitative descriptive. Data collection through interviews, observation and documentation stages. Data validity uses data triangulation which consists of the stages of data collection, data reduction, data presentation and verification. The number of samples used was 1 class III elementary school student. The results of the research prove that parents apply a permissive parenting style in caring for their children with dyslexia, including rules that are not communicated clearly and are not forced, accept all the child's behavior, and obey and liberate the child's abilities. However, parenting styles need to be aligned with the child's progress. This situation can occur because there are several aspects that influence what parenting style will be implemented, parental education, lack of time and attention from parents because both parents work, socio-economic level, and environment. This means that his upbringing is given to his grandmother and older siblings so that the child receives less attention in terms of education. This also has an impact on reading which still stutters because they have to remember and spell the written letters, find it difficult to follow directions, and cannot distinguish letters correctly.